Macroeconomics Linkages on Indonesian Economic Growth: A Granger Causality Analysis - Yusuf, Mochammad (Universitas Dian Nuswantoro Semarang, 2023)
Macroeconomic indicators and trade performance are essential components of developing countries' development as a whole. The upheaval caused by government policies, the economic crisis, and the pandemic that facilitated economic mobility became a major challenge for countries around the world. The aim of this research is to examine the linkages between macroeconomic variables and trade growth in Indonesia using the Error Correction Model and Granger Causality approaches. According to this study, inflation and exchange rates have a significant negative impact on economic growth in the long run. Meanwhile, trade and foreign investment have a significant positive impact on economic growth, both short and long-term. Furthermore, evidence found a bidirectional relationship between inflation and economic growth. Foreign investment and the exchange rate, on the other hand, have a one-way relationship with Indonesian economic growth. Based on the study's findings, it is recommended that the governments of these countries implement measures and policies to manage the real exchange rate, stabilize inflation, and protect economic growth